2009
DOI: 10.1016/j.aop.2009.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical view of pair creation in uniform electric and magnetic fields

Abstract: Pair creation in a uniform classical electromagnetic field (Schwinger mechanism) is studied focusing on the time evolution of the distribution of created particles. The time evolution of the distribution in time-dependent fields is also presented as well as effects of back reaction. Motivated by the Glasma flux tube, which may be formed at the initial stage of heavy-ion collisions, we investigate effects of a magnetic field parallel to an electric field, and find that the magnetic field makes the evolution of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
235
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(252 citation statements)
references
References 66 publications
13
235
1
Order By: Relevance
“…2 Also, in what follows, we take into account neither the collision between the created particles nor their inherent radiation fields. Previous investigations on these subjects have revealed that the effects induced by both phenomena are irrelevant for the PP whenever the field strength E is weaker than the critical one E c [43][44][45] and this is in fact the regime in which we are interested.…”
Section: Quantum Kinetic Approachmentioning
confidence: 97%
“…2 Also, in what follows, we take into account neither the collision between the created particles nor their inherent radiation fields. Previous investigations on these subjects have revealed that the effects induced by both phenomena are irrelevant for the PP whenever the field strength E is weaker than the critical one E c [43][44][45] and this is in fact the regime in which we are interested.…”
Section: Quantum Kinetic Approachmentioning
confidence: 97%
“…We choose 14) where the coefficient is chosen in order to satisfy the normalization condition (2.11). For future reference, we give a useful integral representation of the parabolic cylinder functions,…”
Section: The In-vacuum and The Bogoliubov Coefficientsmentioning
confidence: 99%
“…This quantum state has been extensively discussed in the literature (see, e.g., [10][11][12][13][14] and references therein), but to our knowledge its invariance properties have not yet been studied. We show by a direct calculation that the in-vacuum state is Lorentz invariant.…”
Section: Introductionmentioning
confidence: 99%
“…Our production mechanism of gluons and monopoles is Schwinger mechanism, that is, they are generated as pair production [13,14] under the background color electric and magnetic fields. We assume that the background gauge fields are spatially homogeneous and are pointed into the identical directions, both in real and color spaces.…”
Section: Applicability Of Schwinger Mechanismmentioning
confidence: 99%
“…There are some reliable methods with which the decays of the strong gauge fields can be analyzed. They are classical statistical field theories [10][11][12], Schwinger mechanism [13,14] or classical numerical simulations [15][16][17][18] in gauge theories of quarks and gluons. But there are no reliable methods with which the decays of the weak gauge fields can be analyzed since α s is large.…”
Section: Introductionmentioning
confidence: 99%